GPS Coordinate Estimates by a priori Tropospheric Delays from NWP using Ultra-Rapid Orbits - R. Santangelo; S. Fazlagic'; M. Boccolari (Annals of Geophysics, 2006)
Comparisons of high accuracy GPS positioning estimates using scientific GPS software through three different processing strategies have been done. The two Italian baselines in a time period of 5 months during 2004 made a calculus data set.
For high accuracy GPS differential positioning the employ of global tropospheric delay models can be replaced by the implementation of other techniques. The GPS coordinate repeatability when the tropospheric delay is calculated in near-real time (NRT) from a Numerical Weather Prediction (NWP) model, is experienced. For the NRT approach IGS Ultra-Rapid orbits instead of Precise orbits were used.
Concerning coordinate repeatability, the NWP-based strategy with tropospheric error adjustment appeared as the more accurate (at the submillimetric level) with respect to a standard GPS strategy. Furthermore, several hundreds km long baselines demonstrated the standard deviation at the level of millimeters (from 4.2 to 7.6 mm). Practically, the NWP-based strategy offers the advantage of tropospheric delay estimations closer to realistic meteorological values.
The application of a more accurate meteorology leads to the satisfactory coordinate estimations, and vice versa the well-defined GPS estimations of coordinates may serve as the additional meteorological parameters source.